2013
DOI: 10.1016/j.molonc.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the stromal contribution to Sonic Hedgehog‐dependent pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies. It is typically detected at an advanced stage, at which the therapeutic options are very limited. One remarkable feature of PDAC that contributes to its resilience to treatment is the extreme stromal activation seen in these tumors. Often, the vast majority of tumor bulk consists of non-tumor cells that together provide a tumor-promoting environment. One of the signals that maintains and activates the stroma is the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Moreover, Masugi et al26 found that knockdown of ITGB4 reduced the migration and invasion and that upregulation of ITGB4 promoted cell scattering and motility in pancreatic ductal adenocarcinoma cells. Besides, our study shows that ITGB4 was associated with poor prognosis in HNSCC; similar results have also been shown in pancreatic ductal adenocarcinoma patients 27. Together, we speculate that ITGA6 and ITGB4 in ECM–receptor interaction signaling pathway may play a significant role in HNSCC.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, Masugi et al26 found that knockdown of ITGB4 reduced the migration and invasion and that upregulation of ITGB4 promoted cell scattering and motility in pancreatic ductal adenocarcinoma cells. Besides, our study shows that ITGB4 was associated with poor prognosis in HNSCC; similar results have also been shown in pancreatic ductal adenocarcinoma patients 27. Together, we speculate that ITGA6 and ITGB4 in ECM–receptor interaction signaling pathway may play a significant role in HNSCC.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, stromal cells have been described to act as chaperones for tumor cells that disseminate from the primary tumor, presumably providing a niche for malignant cells that would otherwise be vulnerable during transit (Coleman et al ., ). In addition, we and others have previously shown that the stroma provides a wide array of ligands that act in trans to support tumor cell growth (Damhofer et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…We have previously performed a screen for stromal targets of tumor cell-derived Sonic Hedgehog (SHH), a developmental protein important for the maintenance of stroma in PDAC (Damhofer et al, 2013). From this screen, several extracellular genes were identified that were prognostic, and likely to support tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy, pharmacokinetics, 219 tissue distribution and metabolism of 10058-F4 was analyzed in a 220 prostate cancer xenografts previously [19] and no significant 221 anticancer effect was found after treatment of mice with either 222 20 or 30 mg/kg 10058-F4 due to its rapid metabolism and low 223 concentration in tumors. Dense fibrotic stromal matrix (desmo-224 plasia), which is mainly composed of extracellular matrix, 225 activated fibroblasts and inflammatory cells, is one histological 226 feature of PDAC and together can comprise up to 90% of the tumor 227 volume [20]. Given the poorer vascular and blood perfusion 228 induced by desmoplasia in PDAC, it is reasonable to explain the 229 negative effect of 10058-F4 in vivo.…”
mentioning
confidence: 99%